Analogy in Poems of “Ahmadi Kur” and “Piramerd” - ئیدریس عەبەدوڵڵا مستەفا; جیهان عەبدولوەهاب ئەحمەد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Analogy is one of the Arts of Rhetoric. The Rhetoric, even from ancient times, paid attention on this art. This art consists of resembling one thing to another, for clarifying more and reveal the meaning. It makes what is far close and what is hidden visible. This Art has many types and figures, it makes great examples in literature, therefore, this research will focus on this art. Key words: Analogy, Analogous, Tools, Resemble, Aspect of Similarity. Both poets have examples for most Analogy arts but “Ahmadi Kur” has stronger examples of analogy and he has more examples. The language that is used for analogy by “Ahmadi Kur” has more foreign words as compared to “Piramerd”. Having this art by “Ahmadi Kur” and “Piramerd” is the reason why their poems appear attractive and delicate.